Advances in numerical modelling of tyre fatigue performance: a review - Ayse Mujdeci; Veronica Marchante Rodriguez; Hasher Maqbool; Adam Amadeo; Marzio Grasso (Journal of Materials Science: Materials in Engineering)
Abstract The growing emphasis on sustainability and environmental impact has driven increased demand for eco-friendly tyres. Tyre components are usually subjected to substantial static and dynamic load and often fail due to crack initiation and crack propagation. Understanding of the deformation mechanism of tyre components under fatigue loading is essential for enhancing the safety and reliability of tyres. In recent years, advanced tools for predicting fatigue and wear have been introduced, improving the accuracy of virtual prototyping and enabling more extensive evaluation of design concepts at early stages. This paper reviews recent advancements in the use of numerical methods for predicting fatigue failure and damage in tyre design. Given the limited research on numerical modelling for fatigue and fracture, there is a need for further investigation to develop reliable simulations for predicting tyre behaviour under fatigue loads. This review summarises the current applications of numerical fatigue modelling, providing engineers with a systematic overview of the literature, highlighting key achievements, and promoting further development in the field. The paper begins by discussing tyre components, followed by an exploration of material modelling techniques. It then addresses numerical modelling strategies for full-scale tyres under real-life loading conditions. Challenges in predicting fatigue failure using finite element (FE) modelling are examined, along with the issue of potential damage accumulation. Finally, the paper outlines recommendations for future research on FE modelling techniques, offering insights into current approaches and encouraging further investigation in the field.